1998
DOI: 10.1002/(sici)1097-4547(19980315)51:6<723::aid-jnr6>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Axonal regrowth through a collagen guidance channel bridging spinal cord to the avulsed C6 roots: Functional recovery in primates with brachial plexus injury

Abstract: Intraspinal implantation of a collagen guidance channel (CGC) to promote axon regeneration was investigated in marmosets with brachial plexus injury. After avulsion of the right C5, C6 and C7 spinal roots, a CGC containing (group B) or not (group A) a nerve segment, or a nerve graft (group C), was ventro-laterally implanted into the cord to bridge the ventral horn and the avulsed C6 roots. No spinal cord dysfunction was observed following surgery. Two months later, the postoperative flaccid paralysis of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…An emerging strategy for replacing and/or regenerating damaged tissue is the implantation of stem cells and/or artificial biomaterials such as scaffolds to form tissue bridges between damaged spinal cord stumps. Recent preclinical studies include the implantation of foetal nervous tissue (Bregman, 1987), embryonic stem cells (Brustle et al, 1999), bone marrow mesenchymal stem cells (Prockop, 1997;Akiyama et al, 2002a;Jendelová et al, 2003Jendelová et al, , 2004b, Schwann cells (Kuhlengel et al, 1990), peripheral nervous tissue (Wrathall et al, 1982;Horvat, 1991), collagen-based matrices containing cells or neuroactive substances (Houweling et al, 1998;Liu et al, 1998), nitrocellulose membranes (Houle and Ziegler, 1994), tubes made from polymeric materials (Houle and Ziegler, 1994;Xu et al, 1997;Oudega et al, 2001), polymer hydrogels (Woerly et al, 1998(Woerly et al, , 2001aLesný et al, 2002;Jendelová et al, 2004a), and biodegradable polylactide implants (Maquet et al, 2001).…”
Section: Strategies For Spinal Cord Injury Treatmentmentioning
confidence: 99%
“…An emerging strategy for replacing and/or regenerating damaged tissue is the implantation of stem cells and/or artificial biomaterials such as scaffolds to form tissue bridges between damaged spinal cord stumps. Recent preclinical studies include the implantation of foetal nervous tissue (Bregman, 1987), embryonic stem cells (Brustle et al, 1999), bone marrow mesenchymal stem cells (Prockop, 1997;Akiyama et al, 2002a;Jendelová et al, 2003Jendelová et al, , 2004b, Schwann cells (Kuhlengel et al, 1990), peripheral nervous tissue (Wrathall et al, 1982;Horvat, 1991), collagen-based matrices containing cells or neuroactive substances (Houweling et al, 1998;Liu et al, 1998), nitrocellulose membranes (Houle and Ziegler, 1994), tubes made from polymeric materials (Houle and Ziegler, 1994;Xu et al, 1997;Oudega et al, 2001), polymer hydrogels (Woerly et al, 1998(Woerly et al, , 2001aLesný et al, 2002;Jendelová et al, 2004a), and biodegradable polylactide implants (Maquet et al, 2001).…”
Section: Strategies For Spinal Cord Injury Treatmentmentioning
confidence: 99%
“…Among these manipulations, implantation of a PN graft (Wu et al, 1994a, Holtzer et al, 1996Liu et al, 1998;Chai et al, 2000;Kassar-Duchossy et al, 2001;Rhrich-Haddout et al, 2001) or treatment with neurotrophic factors (Wu et al, 1995, Novikov et al, 1995Oorschot et al, 1998;Watabe et al, 2001) greatly enhanced survival. In those studies, the segment of nerve was usually implanted immediately following root avulsion.…”
Section: Survival Of Spinal Motoneurons Following Axonal Injurymentioning
confidence: 99%
“…24 A variant of a spinal cord bypass without using nerve transfers has been developed in rats 23,24 and later in primates. 20,21 In this model, the proximal terminus of peripheral nerve autografts is implanted into the ventral horn of the spinal cord below the level of injury, whereas the distal ends are anastomosed to the lumbar ventral nerve roots. Data from this model have suggested that anterior horn motor neurons send recovering axons down the nerve grafts to reinnervate the distal lumbar nerve-supplied targets.…”
Section: Spinal Cord Bypass: Animal Studiesmentioning
confidence: 99%